A prediction nomogram for residual after negative pressure aspiration for endogenic cesarean scar ectopic pregnancy: a retrospective study - Yan Lei; Na Zhang; Yu Liu; Xin Du (BMC Pregnancy and Childbirth)
Abstract Background We aimed to establish a predictive nomogram to evaluate the incidence of residual tissue in patients with endogenic cesarean scar ectopic pregnancy after negative pressure aspiration. Methods This retrospective study included patients treated in the gynecology department of our institution from May 2017 to August 2023 who underwent negative pressure suction treatment, ultrasound examinations before and after treatment, and received telephone follow-up for at least 6 months. A total of 899 patients met the inclusion criteria and were divided into a training cohort (629 patients, 70%) and a validation cohort (270 patients, 30%). Independent predictive factors were established using multivariate logistic regression. The resulting nomogram was validated using 1,000 bootstrap resampling, and calibration curves were plotted. Receiver operating characteristic (ROC) analysis was performed to calculate the area under the curve, sensitivity, specificity, and other metrics to assess its discriminative performance. Clinical decision curves were constructed to evaluate clinical applicability and quantify the net benefit within a range of threshold probabilities. The model was externally validated in the validation cohort. Results Predictive factors included in the nomogram included age (hazard ratio [HR]: 1.220, 95% confidence interval [CI]: 1.135—1.316), BMI (HR: 0.890, 95% CI: 0.796—0.986), intraoperative major hemorrhage (HR: 4.457, 95% CI: 1.610—12.292), maximum diameter of the gestational sac (HR: 1.572, 95% CI: 1.295, 1.914), and thickness of the remaining muscle layer of the lower uterine segment (HR: 1.572, 95% CI: 0.014, 0.430). The ROC curve of the resulting nomogram showed similar area under the curve values for the training (0.809, 95% CI: 0.751—0.867) and validation cohorts (0.814, 95% CI: 0.739, 0.888). The Hosmer–Lemeshow test indicated good model fit (P = 0.861), and the calibration curve was close to the ideal diagonal line. Decision curve analysis demonstrated good net benefit, and external validation confirmed its reliability. Conclusions The model may aid in individual clinical decision-making, allowing clinicians to perform immediate postoperative assessments for patients with endogenous ectopic pregnancy in cesarean section scars treated with negative pressure suction, identify high-risk subpopulations, and select appropriate supplementary treatment in advance, making it particularly suitable for low-income areas and resource-limited primary hospitals.